(untitled) (International Journal of Engineering Management Science, 2022)
There is rapid development in the power system applications in early from the 19th century in many areas like transmission, distribution and power system appliances. In the year 1970 there is rapid development in the sector of machines. In late 1970 the first five phase induction motor drive system was proposed the world. Since there is huge research attempts has been placed to develop the multiphase drive systems. The three-phase supply is available from the grid; there is a need to develop a static phase transformation system to obtain a multiphase supply from the available three phase supply. So this paper suggests a novel transformer connection idea to convert the three phase grid supply to a five phase fixed voltage by maintaining the constant frequency supply. Now days the use of five phase motor dive is ever-increasing in commercial purpose and in future also. To satisfy these there are having solutions first, implementation of six phase transmission. To implement this we have to change the three phase to six phase. This paper proposes the implementation of three phase to five phase transformer has been proposed. The five-phase transmission system can be investigated further as an efficient solution for bulk power transfer. The modeling of the five phase transformer is proposed and it is simulated in the Matlab environment.